Morphological and Molecular Characterization of Entomopathogenic Fungi Beauveria spp. Bengkulu Isolate - ginting, Sempurna; Djamilah; Sipriyadi; Permata Sari, Silvia (Bogor Agricultural University, Indonesia, 2025)
Beuveria is a genus of entomopathogenic fungi that plays an important role in controlling agricultural pests. Pest control with entomopathogenic fungi is an alternative to reduce influence the use of chemical insecticides. The diversity of entomopathogenic fungi intraspecies is by the genetic diversity of isolates, a high diversity of isolates can result diversity of fungus virulence. The purpose of this study was to perform the characterization molecular of entomopathogenic fungi Beauveria spp. Bengkulu isolate. Polymerase chain reaction (PCR) was performed for molecular identification Beauveria isolates were obtained from infected larvae in the field (1. Isolate from Coleoptera in Kepahiang, Bengkulu (BBC), 2. Isolate from Hemiptera: Pentatomidae in Rejang Lebong, Bengkulu (BBL), and 3. Isolate from Hemiptera: Alydidae in Taba Mulan, Merigi District, Kepahiang, Bengkulu (MT). The results of the amplification of the entomopathogen Beauveria samples produce DNA bands around ±580 bp. The DNA sequence analysis of ITS 5F and ITS 4R primers showed that the isolates BBC, MT and BBL have fairly high similarity with the Beauveria bassiana isolate 1397, Beauveria bassiana isolate SBI TNSPI, Beauveria bassiana strain B-Bug, Beauveria bassiana voucher TSJBB, Beauveria bassiana isolate SASRI C2, Beauveria bassiana isolate IMI 382764, Beauveria bassiana BCRC:FU31669, Beauveria bassiana isolate B098, Beauveria bassiana isolate INRS-CFL, Beauveria sp. JS-2009a isolate B4B, Beauveria bassiana isolate KACC with the homology of 99.83%, 99.83%, and 98.61%.